2008
DOI: 10.1111/j.1440-1746.2007.05095.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional hepatic recovery after xenotransplantation of cryopreserved fetal liver cells or soluble cell‐factor administration in a cirrhotic rat model: Are viable cells necessary?

Abstract: The positive effects of fetal liver cell and cell-free fetal-specific factors in experimental cirrhosis may result from the presence of stage-specific factors activating hepatocellular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…We presume that transplanted cells secrete growth factors or similar agents that regulate the metabolism and proliferation of host hepatocytes. Ochenashko et al (2008) found that human fetal liver cells and cell-free fetalspecific factors of nonhepatic origin stimulated the recovery processes in an experimental model of CCl 4 -induced cirrhosis in rats. These findings indicate that such effect may result from the presence of stage-specific factors that activate hepatocellular repair.…”
Section: Discussionmentioning
confidence: 98%
“…We presume that transplanted cells secrete growth factors or similar agents that regulate the metabolism and proliferation of host hepatocytes. Ochenashko et al (2008) found that human fetal liver cells and cell-free fetalspecific factors of nonhepatic origin stimulated the recovery processes in an experimental model of CCl 4 -induced cirrhosis in rats. These findings indicate that such effect may result from the presence of stage-specific factors that activate hepatocellular repair.…”
Section: Discussionmentioning
confidence: 98%
“…The effective concentration for BSPC was established in a set of preliminary dose-ranging experiments in which livers were flushed with SPS and a range of bioregulator concenta-tions (10,20,30, and 40 lg of protein/mL of SPS), preserved for 24 h and reperfused.…”
Section: The Experimental Modelmentioning
confidence: 99%
“…In our previous studies the effects of bioregulators of stem and progenitor cells (BSPC) contained in fetal tissue cytosol of mesenchymal-mesodermal origin in several of experimental pathologies were shown [9][10][11]. Our choice of this cell type was due to their well-known unique capacity to produce a wide range of biologically active substances that affect the intra-and extracellular processes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…морфологии печени. Схожие изменения нами были установлены ранее при инъекционном введении криоконсервированных КФП в селезенку крыс с эк-спериментальным циррозом [18]. В совокупности эти данные указывают на высокий терапевтический потенциал КФП.…”
Section: результаты и обсуждениеunclassified